Authority and inquiry in the age of generative AI: A Networked Learning Perspective - Jensen, Camilla Gyldendahl; Dines Petersen, Mads; Nørkjær Gade, Peter (Proceedings of the International Conference on Networked Learning, 2026)
This study examines how generative AI (GenAI) is taken up in students’ academic work and how its use reconfigures authority, inquiry, and legitimacy within networked learning environments. The study adopts a qualitative case study design situated in the Bachelor of Architectural Technology and Construction Management programme at University College of Northern Denmark (UCN), where third-semester students engaged with GenAI tools, including ChatGPT, Copilot, and Primo Research Assistant, while completing an academic assignment. The empirical material comprises reflective process reports and screenshots of students’ interactions with GenAI, collected from 28 project groups across three course iterations. Guided by a networked learning perspective, the analysis focuses on how human and technological actors are positioned within students’ inquiry processes. The findings show that students primarily engaged with GenAI through short, instrumental exchanges used for idea generation, language refinement, and structural support. While GenAI was frequently described as a collaborator, mentor, or “fifth group member,” its role remained largely peripheral to deeper processes of exploration, reasoning, and collective meaning-making, which unfolded through peer dialogue, supervision, and writing outside the AI environment. The study further demonstrates that students selectively delegated linguistic authority to GenAI, valuing its fluency and efficiency, while retaining analytical and epistemic authority over judgment and interpretation. These findings suggest that, rather than displacing human authority, GenAI becomes part of the learning network in ways that reshape how inquiry is initiated and linguistically performed, while leaving core processes of reasoning and collaboration human-centred.